A CLINICAL STUDY OF MUSTA (CYPERUS ROTUNDUS LINN.) IN HYPERLIPIDAEMIA - Kalpana, *R. M; Sitaram, Bulusu (International Journal of Ayurveda and Pharma Research, 2017)
Hyperlipidaemia is a metabolic disorder in population diagnosed by altered levels of Lipoproteins, Cholesterol and Triglycerides in plasma. This results deposition of lipids especially esterified cholesterol in the wall of arteries resulting in the narrowing and blockage of the arteries leading to heart diseases and other diseases such as cerebrovascular disease, renal disease, liver disease and peripheral vascular disease. The present work focused on comparative analysis of anti-hyperlipidaemic profile of Musta (Cyperus rotundus Linn.) in Male and female patients. The patients suffering from Hyperlipidaemia and its related disorders like non-insulin dependent diabetes etc. were divided into two groups, Group A confined to male and Group B confined to female. Each group contains 15 patients. All the patients were advised to take 3 gm powdered Musta rhizome in two or three divided doses for a period of 45 days. After treatment, Musta rhizome powder showed more significant anti-hyperlipidaemic activity in males than females. The significance in males total cholesterol (p<0.05), HDL (p<0.05), VLDL (p<0.05), triglycerides (p<0.05) is more than that of females VLDL (p>0.05), triglycerides (p>0.05). It is observed that in group A 40% patients got complete relief, 6.67 % patients got marked relief, 33.33% patients got moderate relief and 20 % patients got mild relief. Similarly, in group B patients 06.67% patients got complete relief, 6.67 % patients got marked relief, 53.33% patients got moderate relief and 33.33 % patients got mild relief.